1999
DOI: 10.1088/1126-6708/1999/01/008
|View full text |Cite
|
Sign up to set email alerts
|

Center projection with and without gauge fixing

Abstract: We consider projections of SU(2) lattice link variables onto Z 2 center and U(1) subgroups, with and without gauge-fixing. It is shown that in the absence of gauge-fixing, and up to an additive constant, the static quark potential extracted from projected variables agrees exactly with the static quark potential taken from the full link variables; this is an extension of recent arguments by Ambjørn and Greensite, and by Ogilvie. Abelian and center dominance is essentially trivial in this case, and seems of no p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 14 publications
4
66
1
Order By: Relevance
“…Recently we have argued that center dominance by itself does not prove the role of center degrees of freedom in QCD dynamics [20,6]; some sort of center dominance exists also without any gauge fixing and can hardly by attributed to center vortices. Distinctive features of center- (4) and its error is shown in grey.…”
Section: Center Dominance In Su(3) Lattice Gauge Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we have argued that center dominance by itself does not prove the role of center degrees of freedom in QCD dynamics [20,6]; some sort of center dominance exists also without any gauge fixing and can hardly by attributed to center vortices. Distinctive features of center- (4) and its error is shown in grey.…”
Section: Center Dominance In Su(3) Lattice Gauge Theorymentioning
confidence: 99%
“…Recently, the center-vortex picture of confinement has found remarkable confirmation in numerical simulations of the SU(2) lattice gauge theory [3,4,5,6,7,8,9,10,11,12]. Our group has proposed a technique for locating center vortices in thermalized lattice configurations based on fixing to the so called maximal center gauge, followed by center projection [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…one finds a gauge-invariant type of center dominance (see [20] for the SU(2) theory and [21] for the SU(3) theory). Subsequently, it has been noted that this type of center dominance without gauge fixing can in fact be understood in quite simple terms [22], and that furthermore the density of center vortices arising on center-projected lattices without gauge fixing does not exhibit the renormalization group scaling corresponding to a finite physical density [23].…”
Section: Tools and Survey Of Existing Datamentioning
confidence: 99%
“…Subsequently, it turned out that center projection even without previous gauge fixing reproduces the QQ potential, also at short distances, a finding which has somewhat obscured the relevance of the P -vortices for forming the string tension [20]. Moreover, in this case it was observed that other properties of the corresponding vortices (rather than the purely topological features) strongly depend on the bare lattice coupling constant (i.e.…”
Section: Introductionmentioning
confidence: 97%